Memorializing Lynch Victims: Countering Colorblind Ideologies with Experiential Learning. Issue 3 (July 2015) - Bailey, Amy Kate; Leiker, Jason; Gutierrez, Andrew; Larson, Eric C.; Mitchell, Serena
This article describes a class project designed to develop students' abilities to use their sociological imagination to better understand the structural sources of racial inequality. The event consisted of a memorial reading of the names of more than 4, 000 documented lynch victims in the United States. Authors conducted a pretest and posttest on racial attitudes in large Introduction to Sociology courses. Posttest responses evidenced less support for "colorblind" ideologies and greater support for structural sources of inequality.